Diary of an awesome friendly kid : Rowley Jefferson's journal - Kinney, Jeff (Amulet Books, 2019)
Rowley Jefferson, the best friend of Greg Kinney--famous from "Diary of a Wimpy Kid"--now has his own diary about his life and all the fun, awesome, and friendly stuff he gets up to with his parents, during school, and with his best friend, Greg, whether Greg likes it or not.